A Preliminary Study of Alcuin's Bible - Rand, Edward Kennard (Harvard theological review, 1931)
One of the achievements of recent scholarship forever to be identified with Ludwig Traube's name is the combination of history, palaeography, and textual criticism as an indispensable guide to the understanding of early mediaeval culture. The investigator of the course of politics and of letters works at second hand if he knows not the characteristics of those manuscripts in which contemporary events are recorded, or of those in which the treasures of the past were handed down to the Middle Ages. The palaeographer must consider his books not only as specimens of script but as witnesses for the text of the works they contain and as monuments of the culture of the times. The textual critic ploughs an arid field if the codices of an author are to him but A and B and C, to be hung from a stemma according to the value of their readings and their interrelations. These separate studies, which indeed call for diverse methods and diverse trainings, are but parts of a single science—a harmonious and comprehensive view of the life of an epoch. Traube of course had precursors in this complicated art, but his brilliant pursuit of it entitles him to what he himself would disclaim—the rank of a founder.